Model Pendampingan Orang Tua terhadap Kebiasaan Menggosok Gigi menggunakan Wand’s Time Table - Nur Aida, Wanda; Widyastuti, Nugraheni; Nurjanah Tamrin, Ike (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Children's dental health problems are caused by poor children's dental health maintenance behavior. Maintaining oral health in school-aged children still depends on their parents, because parents are the example and role model for every child. The most basic act of maintaining dental and oral health is brushing your teeth. For this reason, it is necessary to instill good and correct teeth-brushing habits. The habit of brushing teeth can be practiced regularly every day and monitored by parents using the wand's time table method. The aim of this study was to determine the effect of parental monitoring on children's tooth brushing habits using the wand's time table method. The type of research is quasi-experimental with a cross-sectional method and a one-group pretest and post-test design. The population was 15 students, while the sample was 20 based on the total sampling technique. From the results of the research carried out, it was found that parental monitoring of children's teeth brushing was partially in the good category, namely 4 respondents. The results of children's habits in brushing their teeth using the wand's time table method were mostly in the very good category, namely 16 respondents. The behavioral results (knowledge, attitudes, and actions) of children in brushing their teeth have increased after monitoring by parents using the wand's time table method, most of which are in the good category and have increased. The results of research conducted at Khalifah 4 Kindergarten show that there is an influence of parental monitoring using the wand's time table method on children's teeth-brushing habits, where ρ = 0.000. It is hoped that parents will gain insight into maintaining dental health in particular. Keywords: Habit; Changes in Behavior; Time Table :